Longitudinal evaluation of repellent activity of Ocimum gratissimum (Labiatae) volatile oil against Simulium damnosum - LPE Usip; KN Opara; ES Ibanga; IA Atting (Memorias do Instituto Oswaldo Cruz, 2006)
To determine the repellent activity of Ocimum gratissimum volatile oil against Simulium damnosum (blackflies), a 12 month (January-December 2003) field study was conducted in three onchocerciasis endemic communities (Idomido, Obio camp, and Ikot Adaha) in Ini Local Government Area of Akwa Ibom State, Nigeria. The result revealed that topical application of 20% (v/v) concentration of the oil with liquid paraffin as a base, reduced the biting rate of S. damnosum by 90.2, 81.6, and 79.7%, in Idomido, Obiocamp, and Ikot Adaha respectively. The oil gave protection against the bite of S. damnosum for at least 3 h. A total of 710 adults S. damnosum were caught by individuals treated with Ocimum oil, as against 4296 caught by the control group. When the flies caught by the treated individuals were dissected none of them was infected with microfilariae of Onchocerca volvulus. Human-vector contact and onchocerciasis transmission could be reduced by the topical application of the volatile oil during the peak biting periods of the vector.